Examining the Interplay Among Indonesian EFL Students’ Digital Literacy, Self-Regulated Learning, and Informal Digital Learning of English - Kurniawati, Atin; Atmojo, Arief Eko Priyo; Swastika, Nilam Febrina; Lutfiana, Salma Ayu (PAEDAGOGIA, 2026)
In today’s digital world, informal digital learning of English (IDLE) has revolutionized English as a foreign language (EFL) learning outside formal classrooms. While numerous studies have increasingly examined potential factors affecting IDLE, associations among digital literacy (DL), self-regulated learning (SRL), and IDLE have been underexamined. The present study seeks to uncover Indonesian EFL students’ levels of DL, SRL, and IDLE, along with the hypothesized relationships among DL, SRL, and IDLE. Drawing on a quota sampling, 391 students responded to DL, SRL, and IDLE questionnaires after providing their informed consent and demographic information. The results demonstrate that Indonesian EFL students enjoy moderate levels of DL, SRL, and IDLE. The results also reveal that DL and SRL, respectively, possess significantly positive relationships with IDLE. Simultaneously, both DL and SRL significantly predict IDLE, explaining 56% of the total variance of IDLE. Ultimately, theoretical and practical implications, as well as future research directions, have been offered.